Behavioral Approaches to Address Gender Inequality in Economic Opportunity - Walsh, Christopher M. (Washington, DC: World Bank, 2022)
Recent innovations in policy interventions have departed from the traditional assumption that people just need sufficient information, adequate incentives (such as lower costs or benefits) or laws for the desired behaviors to happen. The authors have learned that psychological and social factors that influence human behaviors need to be taken into account as they play an instrumental role in the success of development policies and outcomes at every level. Behavioral science - which borrows from anthropology, economics, neuroscience, psychology, and sociology - offers new insights and tools to help policymakers and development practitioners improve upon the design and implementation of policies and interventions - often at low cost - by revealing and addressing patterns of human thinking and behavior normally not accounted for in traditional policy design. The purpose of this note is to offer policymakers and operational teams a simple guide for applying behavioral insights to policies and programs aimed at addressing gender gaps; and a selection of some examples of rigorously evaluated interventions that have successfully addressed drivers of behavior to close specific gender gaps in developing country contexts. Specifically, the note focuses on two dimensions of women’s economic opportunity: women’s participation in the labor force and women’s ownership and control over productive assets.